Relationship between academic performance, psychological well-being, and coping strategies in medical students - Silvina M. Trucchia; Marcela M. Lucchese; Julio E. Enders; Ruth Fernández (Revista de la Facultad de Ciencias Médicas de Córdoba, 2013)
Introduction: Academic performance is a product of the complex environment that surrounds the student, shaped by aspects such as intensity of study, motivation and context of relationships, which affect the academic achievement of individuals. There may be other psychological or emotional factors, such as anxiety, level of psychological wellbeing, and behavior strategies for effective adaptation to concrete environment demands and their associated emotional stress.